1995
DOI: 10.1007/bf00001992
|View full text |Cite
|
Sign up to set email alerts
|

Sexual pattern ofNeocirrhites armatus (Cirrhitidae) with notes on other hawkish species

Abstract: SynopsisWe examined the gonads of eight species in five genera of hawkfishes. Histological preparations of ovaries and testes produced evidence for protogynous hermaphroditism in Neocirrhites armatus and suggested that hermaphroditism may also be expressed in Cirrhitichthys oxycephalus, C. aprinus and C. falco, and possibly also by other species. Sexual patterns in hawkfishes are discussed in relation to environmental and ecological factors which influence mobility and length of spawning season.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
(21 reference statements)
1
10
0
Order By: Relevance
“…There are several theories about the adaptative significance of sex change in those teleosts that normally signals hermaphroditism (Robertson and Warner, 1978;Fischer and Hardison, 1987;Lejeune, 1987;Shapiro, 1987;Siau, 1994;Sadovy and Donaldson, 1995). The occurrences observed in the present study were not common cases of hermaphroditism, but they could be more accurately described as intersexuality.…”
Section: Discussionsupporting
confidence: 46%
“…There are several theories about the adaptative significance of sex change in those teleosts that normally signals hermaphroditism (Robertson and Warner, 1978;Fischer and Hardison, 1987;Lejeune, 1987;Shapiro, 1987;Siau, 1994;Sadovy and Donaldson, 1995). The occurrences observed in the present study were not common cases of hermaphroditism, but they could be more accurately described as intersexuality.…”
Section: Discussionsupporting
confidence: 46%
“…Hawkfishes exist on coral reefs within spatial territories that comprise a polygamous social structure [ 57 , 59 , 60 ]. This study showed that the maximum distance traveled during the observation period for P .…”
Section: Discussionmentioning
confidence: 99%
“…partially accounts for these large-scale differences in patterns of abundance, the local abundance and composition of hawkfish assemblages are likely to be structured by a range of other factors, including inter-specific competition, predation, prey availability and variation in larval supply and settlement of individual species. Many hawkfish species maintain a polygamous social structure with a single dominant male and several smaller subordinate females existing in non-overlapping territories [ 34 , 54 , 56 ]. While it has been hypothesised that territories are maintained to defend optimal microhabitats (e.g., coral colonies), recent evidence suggests that females defend food resources whereas the primary concern of males is defending territories against male conspecifics [ 54 ].…”
Section: Discussionmentioning
confidence: 99%